What renders Bacilli genetically competent? A gaze beyond the model organism - Jakobs, Mareike; Meinhardt, Friedhelm (Applied microbiology and biotechnology, 2015)
Natural genetic competence enables bacteria to take in and establish exogenously supplied DNA and thus constitutes a valuable tool for strain improvement. Extensively studied in the Gram-positive model organism Bacillus subtilis genetic competence has indeed proven successful for genetic manipulation aiming at enhancement of handling, yield, and biosafety. The majority of Bacilli, particularly those relevant for industrial application, do not or only poorly develop genetic competence, although rather homologous DNA-uptake machineries are routinely encoded. Establishing the competent state solely due to high cell densities (quorum sensing dependency) appears to be restricted to the model organism, in which the small signalling peptide ComS initiates the regulatory pathway that ultimately leads to the expression of all genes necessary for reaching the competent state. Agreeing with the lack of a functional ComS peptide, competence-mediated transformation of other Bacilli depends on nutrient exhaustion rather than cell density. Genetically, competent strains of the model organism B. subtilis, cultivated for a long time and selected for laboratory purposes, display probably not least to such selection a point mutation in the promoter of a regulatory gene that favors competence development whereas the wild-type progenitor only poorly displays genetic competence. Consistent with competence being a matter of deregulation, all strains of Bacillus licheniformis displaying efficient DNA uptake were found to carry mutations in regulator genes, which are responsible for their genetic competence. Thus, strain-specific genetic equipment and regulation as well as the proven role of domestication for the well-established laboratory strains ought to be considered when attempting to broaden the applicability of competence as a genetic tool for strains other than the model organism.